Предмет: Алгебра,
автор: tatyana561302
упростите выражение (-3a)^3b^3(5b)^2
Ответы
Автор ответа:
0
(-3а)³b³(5b) ²=-(3a) ³ ×b³ ×25b²=-25(3a) ³ b^5=-25×26a³b^5 =-675a³b^5
Автор ответа:
0
650
Автор ответа:
0
там все правильно
Автор ответа:
0
а -675 это неверно?
Автор ответа:
0
снйчас еще раз пересчитаю
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Английский язык,
автор: ShKamila01
Предмет: География,
автор: abdusattarovabdurasu
Предмет: Математика,
автор: lina6552
Предмет: Обществознание,
автор: husha06
Предмет: Математика,
автор: den6745avatonk